Teaching primary physical education - Lawrence, Julia Clare (SAGE, 2018)
Physical education is an important part of the primary curriculum and one that provides unique challenges for those involved with its teaching. This book offers a balanced and comprehensive overview of the subject, covering issues such as safe practice in PE, inclusion, subject leadership and cross-curricular approaches supported by an accessible theory-informed approach. This second edition includes: links to the new National Curriculum in England, each chapter mapped against the Teachers' Standards, a new chapter on physical literacy and development in the early years and primary ages, a new chapter on health-focused education and the contribution of PE, added case studies in every chapter, enhanced coverage of assessment in PE.